Designing interventions to scaffold emotional awareness, beliefs and action tendencies - Tanmay Sinha (PLoS ONE, 2025)
I demonstrate – via a novel intervention comprising evaluation of emotional contrasting cases and expressive writing – improvements in emotional awareness, beliefs and action tendencies among lower secondary students ( N = 71). Relative to their pre-intervention profiles, students were able to better identify and articulate emotions, as well as showcase a more nuanced understanding of both positive and negative emotions and their respective roles in learning. While the intervention successfully reduced avoidance behaviors towards unpleasant emotions and encouraged a more balanced appraisal of emotional experiences, it also highlighted certain limitations – for instance, students showed little change in their acceptance of unpleasant emotions, suggesting further support may be needed to fully utilize emotions as learning tools.